Antidiabetic Effect of Sida cordata in Alloxan Induced Diabetic Rats - Shah, Naseer Ali (Hindawi Publishing Corporation, 2014)
Medicinal plants are efficient ameliorator of oxidative stress associated with diabetes mellitus. In this study, ethyl acetate fraction (SCEE) of Sida cordata was investigated for scientific validation of its folk use in diabetes. Antidiabetic effect of SCEE was confirmed by antihyperglycemic activity in normal glucose loaded and diabetic glucose loaded animals as well as normal off feed animals. Confirmation of antidiabetic activity and toxicity ameliorative role of S. cordata was investigated in a chronic multiple dose treatment study of fifteen days. A single dose of alloxan (120 mg/kg) produced a decrease in insulin level, hyperglycemia, elevated total lipids, triglycerides, and cholesterol and decreased the high-density lipoproteins. Concurrent with these changes, there was an increase in the concentration of lipid peroxidation (TBARS), H(2)O(2), and nitrite in pancreas, liver, and testis. This oxidative stress was related to a decrease in glutathione content (GSH) and antioxidant enzymes. Administration of SCEE for 15 days after diabetes induction ameliorated hyperglycemia, restored lipid profile, blunted the increase in TBARS, H(2)O(2), and nitrite content, and stimulated the GSH production in the organs of alloxan-treated rats. We suggested that SCEE could be used as antidiabetic component in case of diabetes mellitus. This may be related to its antioxidative properties.